Mindfulness and compassion training in adolescence: A developmental contemplative science perspective. Issue 142 (June 2014) - Roeser, Robert W.; Pinela, Cristi
Abstract : Adolescence is a developmental period of risk, as well as a window of opportunity for cultivating positive development and thriving. It is characterized by simultaneous changes in the brain, body, mind, and social domains that offer a platform for building new skills and habits. This chapter discusses the role that secular forms of mindfulness and compassion training may play in fostering positive development in adolescence. The emerging discipline of "Developmental Contemplative Science" (DCS) is introduced, the theoretical and empirical basis of mindfulness in adolescence is illustrated in depth, and secular mindfulness and compassion practices for youth are portrayed. Last, this chapter offers an agenda for future research on connecting mindfulness to key developmental domains in adolescence.